2009
DOI: 10.1002/pssb.200880353
|View full text |Cite
|
Sign up to set email alerts
|

Optical instabilities in semiconductor quantum‐well systems driven by phase‐space filling

Abstract: Four‐wave mixing (FWM) is one of the best known phenomena in semiconductor optics. Recent experimental results of FWM instabilities and optical switching in atomic systems have renewed the interest in FWM and possible related instabilities in semiconductors. We have recently performed theoretical investigations of FWM instabilities in a variety of semiconductor quantum well systems (single quantum wells, Bragg‐spaced multiple quantum wells, and planar semiconductor micocavities) and shown that different system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…(14) for the semiconductor quantum well keeping only the atomic nonlinearities (PSF). For this case, an analytical evaluation using first-order (in the pump field amplitude) pump polarizations has been discussed in [71]. It was found that instability driven only by PSF cannot be expected.…”
Section: Instabilities In Single Quantum Wellsmentioning
confidence: 97%
“…(14) for the semiconductor quantum well keeping only the atomic nonlinearities (PSF). For this case, an analytical evaluation using first-order (in the pump field amplitude) pump polarizations has been discussed in [71]. It was found that instability driven only by PSF cannot be expected.…”
Section: Instabilities In Single Quantum Wellsmentioning
confidence: 97%